Evaluation of oral health education program on knowledge, attitude and practice among Isfahan primary school's teachers in 2019 - Bita Heydarzadeh; Bahareh Tahani; Imaneh Asgari (Tehran University of Medical Sciences, 2021)
Background and Aims: School teachers have key role in providing the basic health information for their students, and their knowledge, attitude, and practice affect children's oral health through developing of the healthy behaviors. The goal of this study was to evaluate the effectiveness of an oral health education program for primary school teachers on their knowledge, attitude, and practice fields in the framework of oral health promoting schools. Materials and Methods: This quasi-experimental pre-post study was conducted among five oral health promoting schools in Isfahan city in 2019. A validated and reliable questionnaire including four sections of demographic data, knowledge, attitude, and practice was applied for data collection. The questionnaire contained 24 knowledge, 9 attitudes, and 5 practice questions. It was distributed among 63 enrolled teachers at base line and two months later after two educational-emotional workshops. Before and after data were analyzed by SPSS21 (α=0.05) by related samples Wilcoxon signed rank test and background variables by Kruskall-wallis test. Results: After the educational intervention, their knowledge score increased significantly from 14.1±3.8 to 18.5±3.7 (P<0.001). About 34% of teachers had a high level of knowledge proficiency at the beginning of the study which eventually rose to 76%. Teachers' attitude decreased significantly from 34.6±5 to 31.4±4.6 (P<0.001). At the beginning of the study, 89% of them had a positive attitude towards oral health programs which decreased to 84% at the end of the study. In the performance part, 63.5% of the teachers paid attention to the fluoride in their toothpaste which reached 87.3% after the workshop and the teachers' performance score increased from 3.07 to 3.39 after the intervention (P<0.012). Conclusion: The package of educational intervention for teachers in oral health-promoting schools improved the level of knowledge and practice, but slightly reduced the level of attitude. However, due to the importance of changing attitudes in teachers and the existence of structural and programmatic barriers to integrate the health issues into school education, other models need to be evaluated and compared.